"Bamboos", Trinidad, B.W.I - W.C. Ross and Co.Ltd (My University, 2010)
Here bamboo is growing in a swampy area somewhere in Trinidad.
Colour: Black and white; Style: Portrait; Other: Bordered, Undivided
Keywords: Trinidad and Tobago; Postcards; Bamboo--Trinidad and Tobago